The Impact of Digital Transformation on Corporate Financial Investments: A Literature Review - Muhammad Rizal; Ruslaini Ruslaini; Grace Yulianti; Sri Utami Nurhasanah (Cahaya Abadi Publisher, 2025)
This study investigates the influence of digital transformation on corporate financial investments using a qualitative literature review approach. Digital transformation significantly affects investment decision-making, capital allocation, and operational efficiency. The integration of findings from previous research reveals that digital technologies encourage companies to shift focus toward intangible assets such as information systems and data analytics. However, challenges like resource limitations and readiness for adoption persist. Furthermore, government policies and digital skill development are critical in facilitating this transition. The findings provide valuable insights for companies and policymakers to leverage digital technologies for enhancing efficiency and competitiveness in the digital era.